A simple, modular synthesis of C4-substituted tryptophan derivatives. Issue 42 (10th October 2016) - Bartoccini, F.; Bartolucci, S.; Mari, M.; Piersanti, G.
Abstract : A straightforward, rapid, versatile, regio- and chemoselective approach for the synthesis of C4-substituted tryptophan derivatives is reported. Abstract : The modular and versatile synthesis of C4-substituted tryptophan derivatives by direct functionalization of easily available N -acetyl 4-boronate tryptophan methyl ester via transition metal-catalyzed and metal-mediated cross coupling reactions is described. The versatility of the chemistry is highlighted by the gram-scale synthesis of 4-boronated N -acetyl-tryptophan methyl ester and the rapid synthesis of C4-aryl, C4-alkyl, C4-cyano, C4-trifluoromethyl, C4-azido, and C4-hydroxy tryptophan derivatives. The utility of our methodology is illustrated through the quick approach to the tricyclic azepino indole skeleton embedded in many natural products.